THE UPDATE MEDICATION ON HIGH CHOLESTEROL - Eman Hafiz Ibrahim; Samyah Meshal Alshammari; Manal Halal Alanazi; Haya Mohmmed Alqousi; Noura Howidi Aldosari; Awatef Fahat Alanezi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This essay aims to provide an update on the medication for high cholesterol, a common medical condition affecting individuals worldwide. High cholesterol levels pose a significant risk for cardiovascular diseases, including heart attacks and strokes. The essay will explore the current advancements in medication for high cholesterol, focusing on statins, PCSK9 inhibitors, and other emerging therapies. The results from recent studies, clinical trials, and meta-analyses will be discussed to highlight the effectiveness and safety profiles of these medications. Furthermore, the essay will analyze the benefits and potential side effects of each medication, providing a comprehensive understanding of the treatment options available. The conclusion will summarize the findings and emphasize the importance of medication adherence and lifestyle modifications in the management of high cholesterol.